Cover Image, Volume 114, Number 6, June 2017. Issue 6 (June 2017) - Goers, Lisa; Ainsworth, Catherine; Goey, Cher Hui; Kontoravdi, Cleo; Freemont, Paul S.; Polizzi, Karen M.
Abstract : Cover Legend The cover image, by Lisa Goers et al., is based on the Article Whole‐cell Escherichia coli lactate biosensor for monitoring mammalian cell cultures during biopharmaceutical production, DOI:10.1002/bit.26254 .